Rheumatoid arthritis-associated rheumatoid factors post-COVID-19 - Titi, Adam H.; Krisko, Braedon T.; Bashar, S. Janna; Adyniec, Ryan R.; Parker, Maxwell H.; Murren, Nat F.; Myhr, Courtney B.; Shelef, Miriam A. (Frontiers in Immunology, 2025)
ObjectiveRheumatoid factors (RFs) are a hallmark of rheumatoid arthritis but also arise in infections, including COVID-19. Moreover, infections, again including COVID-19, are associated with rheumatoid arthritis development, positioning RFs as a potential link between infection and rheumatoid arthritis. RFs traditionally have been thought to be relatively uniform in their reactivity across conditions apart from some increased reactivity in rheumatoid arthritis. Recently, however, IgG RFs that bind citrulline- and homocitrulline-containing IgG epitopes were identified in rheumatoid arthritis, but not other autoimmune diseases, whereas IgM RFs that bind specific native linear IgG epitopes were found uniquely post-COVID-19. The objective of this study was to determine if rheumatoid arthritis-associated RFs develop post-COVID-19 in order to provide new insights into post-infection immune tolerance loss.MethodsCOVID-19 convalescent, rheumatoid arthritis, and control sera (n=20) were used in enzyme-linked immunosorbent assay to evaluate IgG, IgM, and IgA binding to eight IgG1-derived peptides in their native, citrulline-containing, and homocitrulline-containing forms. Antibody levels were compared by Kruskal-Wallis test with Dunn’s multiple comparisons test, and the number of participants with binding greater than all controls was compared by Fisher’s exact test.ResultsIgG binding to seven of the eight IgG1-derived peptides was increased in a citrulline- or homocitrulline-specific manner only in rheumatoid arthritis. IgA binding was increased to five of eight IgG1-derived peptides in a citrulline- or homocitrulline-specific manner in rheumatoid arthritis and to one homocitrulline-containing peptide post-COVID-19. More post-COVID-19 participants than controls had elevated IgG or IgA binding to two IgG1-derived peptides in a homocitrulline-specific manner.ConclusionRheumatoid arthritis-associated RFs are primarily restricted to rheumatoid arthritis, but some individuals post-COVID-19 generate moderate levels of a few rheumatoid arthritis-associated RFs, especially of the IgA isotype and homocitrulline-reactive. These findings refine our understanding of RFs, provide novel insights into loss of immune tolerance post-infection, and reveal new possibilities for biomarker development in preclinical rheumatoid arthritis.